La segnalazione dei danni provocati dal terremoto attraverso modalità innovative: Web 2.0 e crowdsourcing - Prunesti, Alessandro (GEOmedia, 2013)
La sequenza sismica verificatasi in Emilia Romagna, Lombardia e Veneto a partire dal Maggio 2012, culminata con ledue tragiche scosse del 20 e 29 maggio, ha provocato 27 morti, 350 feriti e 16.000 senzatetto. Sono stati finora valutatidanni per 13,2 miliardi di Euro. Abstract A seismic sequence occurred in Emilia Romagna, Lombardia and Veneto regions since May 2012. The culminating events were two tragic mainshocks on May 20th and May 29th, resulting in 27 dead, 350 injuried and over 16,000 homeless. As of this writing, a total damage of 13.2 billion euros was assessed. Unfortunately, catastrophic consequences of earthquakes are not uncommon in Italy. The 2012 seismic sequence was one among the first cases in which social network and communication technologies were used to convey information about tragedy and to support rescue operations as well as self-organization of affected communities.